Interaction of magnetic nanoparticles with U87MG cells studied by synchrotron radiation X‐ray fluorescence techniques. (14th May 2013) - Gianoncelli, A.; Marmorato, P.; Ponti, J.; Pascolo, L.; Kaulich, B.; Uboldi, C.; Rossi, F.; Makovec, D.; Kiskinova, M.; Ceccone, G.; Streli, Christina; Markowicz, Andrzej
<x xml:space="preserve">Abstract</x> Synchrotron radiation (SR) X‐ray microscopy combined with X‐ray fluorescence (XRF) microspectroscopy provides unique information that have pushed the frontiers of biological research, particularly when investigating intracellular mechanisms. This work reports an SR‐XRF microspectroscopy investigation on the distribution and the potential toxicity of Fe2O3 and CoFe2O4 nanoparticles (NPs) in U87MG glioblastoma‐astrocytoma cells. The U87MG cells exposed to NPs concentrations ranging from 5 to 250 µg/ml for 24 h were analyzed in order to monitor both morphological and chemical changes. The SR‐XRF maps complemented with XRM absorption and phase contrast images have revealed different intracellular distribution patterns for the two nanoparticles types allowing different mechanism of toxicity to be deduced. Copyright © 2013 John Wiley & Sons, Ltd.